The Europa year book 2003 (London Europa Publications, 2003)
It is a reference material with information on the political, economic and commecial institutions of the world. It has two volumes with volume 1 focusing on international organizations and the countries of Europe. Volume II lists the remaining countries of the world from Cameroon to Zimbabwe
Includes index
nju 17/03/2020
Ref